Reviu Gambaran Perbedaan Perilaku dalam Latar Belakang Multikultural Lintas Budaya - Qanita Audrey Apsarini; Mutia Husna Avezahra (Flourishing Journal, 2023)
The behavior of children and adolescents can vary from the background of the social, cultural, and economic environment where the child is raised. This literature review raises the topic of the behavior of people within different cultural backgrounds and several other aspects, such as socio-economics, from all over the world. This literature review aims to find out about the description of differences in children's backgrounds that can have impacts on certain aspects of children during their development periods that might affect their adult selves. This literature review was compiled by collecting a number of related and relevant articles regarding the differences shown in the development of children from various backgrounds around the world over the past 15 years that have been posted previously through several online journal database pages that the author can freely access. The author categorizes the results of this literature review into three parts, namely differences between cultures in Western countries (America and Europe), in Western versus non-Western countries (Africa versus Africa/America/Europe), and only in between Asian countries (Indonesia, Singapore, and Israel). AbstrakPerilaku anak-anak dan remaja dapat bervariasi dari bagaimana gambaran latar belakang lingkungan sosial, budaya, dan ekonomi dimana anak dibesarkan. Kajian literatur ini mengangkat topik mengenai perilaku manusia dengan latar belakang budaya, dan beberapa aspek lainnya seperti sosioekonomi, dari seluruh penjuru dunia. Kajian literatur ini bertujuan untuk mencari tahu mengenai bagaimana gambaran perbedaan latar belakang anak dapat berdampak pada aspek-aspek tertentu dalam diri anak pada masa perkembangannya sehingga berpengaruh pada diri dewasanya. Kajian literatur ini disusun dengan mengumpulkan sejumlah artikel yang berkaitan dan relevan mengenai perbedaan yang ditunjukkan dalam perkembangan anak dari berbagai latar belakang di penjuru dunia selama 15 tahun terakhir yang telah diunggah sebelumnya lewat beberapa laman online journals database yang dapat secara bebas diakses penulis. Penulis dapat mengkategorikan hasil kajian literatur yang diperoleh menjadi tiga bagian yaitu perbedaan antarkultur dalam negara di Barat (Amerika dan Eropa), dalam negara di Barat versus non-Barat (Afrika/Amerika/Eropa versus Asia), dan hanya dalam antarnegara di Asia saja (Indonesia, Singapura, dan Israel).